Generalized fuzzy trees - Biswajit Sarkar; Sovan Samanta (International Journal of Computational Intelligence Systems, 2017)
Graphs are the backbone of many real systems like social networks, image segmentation, scheduling, etc. To input uncertainty to such systems, generalized fuzzy graphs are used. Generalized fuzzy tree is one generalized fuzzy subgraph of a generalized fuzzy graph which characterizes the whole graph. In this study, generalized fuzzy trees are introduced. The concepts of strongly connectedness, nearly disconnect, distance between two nodes, bridges are exemplified.